COMPARISON OF DENTIN HYPERSENSITIVITY MANAGEMENT OF EXPOSED ROOT SURFACES BY DENTIN BONDING AGENT AND THINLY APPLIED GLASS IONOMER CEMENT: A CLINICAL TRIAL - Akbar, Iftikhar; Huma Kamal,; Ashfaq Azim, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Dentin hypersensitivity is a common clinical problem all over the world and it is called the common cold of dentistry. This study aimed to compare the efficacy of glass ionomer cement and dentin bonding agent in management of dentin hypersensitivity in patients presenting to X Dental College. Methods: This Quasi-experimental study was conducted on patients presented to the Department of Operative dentistry and Endodontics from February to August 2022. A total of 60 patients in the age range of 18-70 were selected based on convenience sampling. The patients were divided into 2 groups. Group A received glass ionomer cement and Group B received dentin bonding. The sensitivity was evaluated before treatment using visual analogue scale and documented as baseline reading by using tactile and evaporative stimuli, then immediately after treatment and after 1 and 6 week using visual analogue scale by using tactile & evaporative stimuli.